2015
DOI: 10.1016/j.annemergmed.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Among Cognitively Intact, Noncritically Ill Older Adults in the Emergency Department

Abstract: Objectives We estimate the prevalence of malnutrition among older patients presenting to an emergency department (ED) in the southeastern United States and identify subgroups at increased risk. Methods We conducted a cross-sectional study with random time block sampling of cognitively intact patients aged 65 years and older. Nutrition was assessed using the Mini Nutritional Assessment Short-Form (0–14 scale) with malnutrition defined as a score of 7 or less and at-risk for malnutrition defined as a score of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…Among older adults presenting to three EDs in distinct areas of the US, the prevalence of malnutrition was estimated to be 12%. This value is within the range of a prior estimate by our group (16%; 95% CI 11%, 23%; n = 138) and is similar to that from a study conducted in Australia (15%; 95% CI 9%, 21%) . These estimates are more than double the estimated prevalence of malnutrition in community‐dwelling older adults (5.8%), supporting the idea that EDs provide access to a nutritionally vulnerable subset of older patients .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Among older adults presenting to three EDs in distinct areas of the US, the prevalence of malnutrition was estimated to be 12%. This value is within the range of a prior estimate by our group (16%; 95% CI 11%, 23%; n = 138) and is similar to that from a study conducted in Australia (15%; 95% CI 9%, 21%) . These estimates are more than double the estimated prevalence of malnutrition in community‐dwelling older adults (5.8%), supporting the idea that EDs provide access to a nutritionally vulnerable subset of older patients .…”
Section: Discussionsupporting
confidence: 86%
“…These estimates are more than double the estimated prevalence of malnutrition in community‐dwelling older adults (5.8%), supporting the idea that EDs provide access to a nutritionally vulnerable subset of older patients . Despite the fact that malnutrition screening takes less than 5 minutes to complete, screening is rarely performed. While a majority of malnourished patients in our study were admitted, 21% of malnourished participants were discharged home from the ED without any formal assessment or treatment for malnutrition.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Attention to the non-medical problems such as social isolation, malnutrition, poor health literacy, and neglect, which have strong influences on health behaviors and outcomes may be necessary to meet older adults’ needs and reduce EMS demand in this population. 46,47 Patients with these problems might benefit from education regarding alternatives to calling 911 for these symptoms or efforts to develop non-EMS transport options. Additionally, alternative healthcare delivery models such as mobile integrated health care and community paramedicine programs have been proposed and are currently being studied, particularly for patients with chronic conditions such as congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on a random sample of "cognitively intact, non-critically, ill older adults" in an emergency department found that over half were malnourished or at risk for malnutrition, and the majority of the malnourished patients had not been previously diagnosed with the condition. The researchers concluded that the growing role of emergency departments as sites of care and entry point makes them essential places for identifying and addressing unmet needs such as malnutrition for older adults [75]. In this regard, a simple "vital sign" for malnutrition screening would facilitate the nurse's work.…”
Section: Community Interventionsmentioning
confidence: 99%